2022
DOI: 10.1186/s13567-022-01051-y
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq analysis of duck embryo fibroblast cells gene expression during duck Tembusu virus infection

Abstract: Duck Tembusu virus (DTMUV), a member of the family Flaviviridae and an economically important pathogen with a broad host range, leads to markedly decreased egg production. However, the molecular mechanism underlying the host-DTMUV interaction remains unclear. Here, we performed high-throughput RNA sequencing (RNA-Seq) to study the dynamic changes in host gene expression at 12, 24, 36, 48 and 60 h post-infection (hpi) in duck embryo fibroblasts (DEF) infected with DTMUV. A total of 3129 differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The second-generation sequencing RNA-seq has been widely used in oncology, immunology, and cell biology in recent years ( 22 , 23 ). To clarify the differences in gene expression in the duck immune cells, we applied the RNA-seq transcriptome sequencing technology to analyze the gene expression differences in the duck monocytes/macrophages cell model infected with DPV CHv strain or CHa strain at 48 hpi.…”
Section: Resultsmentioning
confidence: 99%
“…The second-generation sequencing RNA-seq has been widely used in oncology, immunology, and cell biology in recent years ( 22 , 23 ). To clarify the differences in gene expression in the duck immune cells, we applied the RNA-seq transcriptome sequencing technology to analyze the gene expression differences in the duck monocytes/macrophages cell model infected with DPV CHv strain or CHa strain at 48 hpi.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, renal tubular epithelial ( RTE ) cells are a promising option for GAstV-2 proliferation and pathogenesis analysis. RNA sequencing ( RNA-seq ), a powerful approach that can provide precise measurements for transcriptome profiling, can reveal dynamic changes in host gene expression during pathogen infections, including various viral infections ( Ma et al, 2021 ; Pan et al, 2022 ; Perlas et al, 2021 ). Therefore, in the current study, we isolated goose primary RTE ( GRTE ) cells from goose embryos and investigated GAstV-2 growth characteristics in GRTE cells and GAstV-2–GRTE cell interactions through RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…Its single open reading frame (ORF) encodes a unique polyprotein precursor, which is then cleaved into three structural proteins (C, prM, and E) and seven non-structural (NS) proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5) [ 15 , 16 ]. Previous studies have shown that DTMUV infection can effectively trigger type I IFN signaling and downstream ISG expression [ 17 , 18 ]. Avian type I IFNs and ISGs, such as VIPERIN, IFIT5, CMPK2, IRF7, IRF1, Mx, and OASL, play important roles in combating DTMUV infection [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%